Social Work competencies in Matrix Support in Mental Health / As competências do Serviço Social no Apoio Matricial em Saúde Mental (Argumentum, 2018)
The Support Matrix is technical-pedagogical support technology and back-stop assistance to Primary Healthcare, provided for within the Unitary Health System (Sistema Único de Saúde (SUS)), which questions the hegemonic organisational and technical-assistance model, proposing links and support among teams with a view to delivering integration and Care resolution.  It implies that professional Social Work actions in Mental Health Support Teams have been built and legitimised historically in the field of public policy.  Social workers and managers agree that the social worker translates social reality, from the interdisciplinary and inter-sectorial perspective, providing concreteness, directional and visibility to the profession, and form part of the set of professional actions within the SUS.Keywords: Health Policy. Mental Health Policy. Unitary Health System. Matrix Support.Social Work.